CULTIVATING RESILIENCE AND INCLUSION: AN IN-DEPTH ANALYSIS OF MOROCCO’S "GÉNÉRATION GREEN" STRATEGY AS A DRIVER FOR AGRICULTURAL TRANSFORMATION - Oussama ELMIMOUNI (IJRDO - Journal of Business Management, 2025)
This paper offers a comprehensive examination of Morocco’s "Génération Green" 2020-2030 strategy, assessing its role as a transformative framework for achieving sustainable performance within the nation’s critical agricultural sector. Moving beyond the production-centric achievements of its predecessor, the "Plan Maroc Vert," this new strategy signals a paradigm shift towards a model that prioritizes human capital development, social equity, and ecological resilience. Utilizing a mixed-methods methodology, this research synthesizes longitudinal national data with original survey findings from a diverse sample of 180 Moroccan agribusinesses and smallholder farmers. The study develops a composite index to evaluate the adoption of the strategy’s core pillars. The results demonstrate a significant positive correlation between the depth of adoption of these pillars and enhanced performance metrics, including substantial increases in farmer income, notable improvements in water use efficiency, and stronger market positioning. Conversely, the analysis brings to light considerable implementation challenges, such as a pervasive digital divide, constrained access to finance for smaller actors, and pronounced regional disparities. The paper concludes that while "Génération Green" provides a visionary and robust blueprint for the future, its ultimate success hinges on fostering more decentralized, participatory governance and pioneering inclusive financial mechanisms.